Pengaruh Model Pembelajaran Kooperatif Tipe Make A Match Terhadap Keaktifan Belajar PAI Siswa Di SMPN 03 Sungai Pua - Fina Fanduwinata; Nurhasnah Nurhasnah; Jasmienti Jasmienti; Alimir Alimir (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2023)
This research was conducted at SMPN 03 Sungai Pua which was motivated by several problems, which the authors found in class VIII SMPN 03 Sungai Pua. Where in the learning process there is a lack of student activeness in PAI learning, the learning process only uses the lecture method and there are no interesting methods used in learning, learning is still teacher-centered which causes students to tend to be less active, and there are still many Grade VIII students who have not received maximum learning outcomes so that the quality of learning must be improved again. This research is a quantitative experimental research. This research is located at SMP Negeri 03 Sungai Pua. The population in this study amounted to 54 students. The sampling technique used is the random sampling technique. The instruments used in this study were questionnaires and documentation. Based on the results of the research that has been done, it shows that there is an influence of the make a match type of cooperative learning model on the activeness of students' PAI learning at SMP Negeri 03 Sungai Pua.